Effecs of SMEs in expanding sustainable livelihoods in Bindura urban - Mafuta, Sollow (Midlands State University, 2018)
The purpose of the study was to explore the effects of SMEs on improving sustainable livelihoods in Zimbabwe and also to establish the challenges faced by the entrepreneurs that inhibit the growth of the sector. SMEs are the major economic drivers of Zimbabwe due to the outstanding impacts that include employment creation, wealth generation amongst others. A survey was carried out on a sample of 80 SMEs from the provincial town of Mashonaland Central that is Bindura Urban. The impacts of SMEs were measured in terms of empowerment, income generation as well as employment. The SMEs varied from retailing to services. Statistical data analysis was carried out to bring about the effects of these SMEs as well as the challenges they are facing. Findings show that indeed SMEs contributed significantly to employment creation and revenue accumulation. Major challenges hampering their growth included lack of access to finance, regulatory environment, competition and technology. Based on findings, the study provides some suggestions and recommendations that sought to enhance the growth of the SMEs. Policy makers are urged to smoothen the regulatory system so as to ease the way of doing business. Capacity building should also be vitalized so as to encourage entrepreneurship skills amongst owners and managers of SMEs to ensure growth and above all financial inclusivity to dovetail accelerated growth of small businesses.